Exploring the impact of social media marketing on consumer brand engagement in fashion branded jewellery - Leow, Yi Ling (2025)
Social media marketing has changed the way brands connect with customers, especially in the fashion branded jewellery industry in Malaysia. This study will use the timulus Response Theory to understand how brand’s marketing efforts on social media influence consumer engagement. The study focuses on social media marketing activities like entertainment, interaction, electronic word-of-mouth and trendiness as the "stimuli" and looks at how these lead to consumer brand engagement as the "responses." Data will be collected from 195 respondents through surveys and analyzed using SPSS software. This study can provide useful ideas for marketers to improve their social media strategies and stay ahead in the competitive fashion branded jewellery market. The research also will offer guidance for future studies to better understand how social media marketing affects consumer brand engagement.